2022
DOI: 10.1186/s12877-022-03027-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and comorbidities of headache in patients over 50 years of age: a cross-sectional study

Abstract: Background Although headache is a common complaint in younger individuals, it is one of the most common complaints among persons over the age of 50 and is a significant cause of morbidity. As there are differences in the causes and types of headache, the diagnosis and management of headache in older adults differ from that in younger individuals. Methods In this cross-sectional study, 570 patients ≥ 50 years were recruited at a university affiliate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
5
0
4
Order By: Relevance
“…Additionally, older individuals are often faced with age-related physiological changes, such as slowing of gastric emptying, and an altered drug metabolism rate [24]. The long-term use of medications for chronic conditions like diabetes, hypertension, thyroid, and arthritis may exacerbate migraine symptoms or trigger migraine, thereby stressing the special attention that is needed when developing treatment plans in these individuals [6,25]. With an increase in the global life expectancy, there is a shift towards finding optimal solutions to manage health problems in an aging population.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, older individuals are often faced with age-related physiological changes, such as slowing of gastric emptying, and an altered drug metabolism rate [24]. The long-term use of medications for chronic conditions like diabetes, hypertension, thyroid, and arthritis may exacerbate migraine symptoms or trigger migraine, thereby stressing the special attention that is needed when developing treatment plans in these individuals [6,25]. With an increase in the global life expectancy, there is a shift towards finding optimal solutions to manage health problems in an aging population.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, 11 population-based surveys [ 6 , 7 , 12 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 22 ], 2 headache clinic surveys [ 32 , 33 ], and 2 insurance data surveys [ 34 , 35 ] were conducted to investigate the headache disorder prevalence in the elderly ( Table 5 ). The headache disorders prevalence was about 12–76%, migraine prevalence 1–11%, CDH prevalence 1.6–53.4%, and MOH prevalence 0.70–2.60% worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Another article (7) focused on the controversial relationship between hypertension and migraine and returned to the theory that considered there is a relationship. A cross sectional study was applied to demonstrate the comorbidities of headache in older patients, and one of the comorbidities was hypertension (8). Another study revealed that migraine had a link with cardiovascular events in the presence of hypertension among type 2 diabetic patients (9).…”
Section: Most Used Abstractmentioning
confidence: 99%